2019
DOI: 10.18410/jebmh/2019/300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Chelating Agents as Final Rinse on Intracanal Smear Layer Removal at the Apical Third Area of Single Rooted Teeth Using Apical Negative Pressure: An in Vitro Sem Study

Abstract: BACKGROUNDSmear layer formed by mechanical action of endodontic instruments is the potential source of microbial infection. Various chelating actions have been used for managing the smear layer but none of them showed promising results at the apical third of root canal. The purpose of this study was to evaluate the intracanal smear layer removal efficacy of 10% citric acid, 7% maleic acid and 17% EDTA at the apical third area of single rooted teeth when irrigated with apical negative pressure system. METHODSEi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This finding is contrast to the study done by Choudhary et al . [ 34 ] who reported that both citric acid and maleic acid are equally effective in removing the smear layer from all parts of root dentin.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is contrast to the study done by Choudhary et al . [ 34 ] who reported that both citric acid and maleic acid are equally effective in removing the smear layer from all parts of root dentin.…”
Section: Discussionmentioning
confidence: 99%